Respuesta :
Hello!
The problem has asked that we simplify the given expression using the Distributive Property. The Distributive Property states the following:
a(b + c) = ab + ac
a(b – c) = ab – ac
In this case, we’ll use the second of the two formulas listed above. Let’s begin by inserting any known values given in the original problem:
a(b – c) = ab – ac
5(2x – 5) = 5(2x) – 5(5)
Now simplify the right side of the equation:
5(2x) – 5(5) = 10x – 25
We have now proven that 5(2x – 5) is equal to 10x – 25. Therefore, the correct answer is C.
I hope this helps!
The problem has asked that we simplify the given expression using the Distributive Property. The Distributive Property states the following:
a(b + c) = ab + ac
a(b – c) = ab – ac
In this case, we’ll use the second of the two formulas listed above. Let’s begin by inserting any known values given in the original problem:
a(b – c) = ab – ac
5(2x – 5) = 5(2x) – 5(5)
Now simplify the right side of the equation:
5(2x) – 5(5) = 10x – 25
We have now proven that 5(2x – 5) is equal to 10x – 25. Therefore, the correct answer is C.
I hope this helps!